Strategic Point-of-Care Requirements of Hospitals and Public Health for Preparedness in Regions At Risk - Kost, Gerald J. (2012)
OBJECTIVES: To study health resources and point-of-care (POC) testing requirements for urgent, emergency, and disaster care in Phang Nga Province, Thailand; to determine instrument design specifications through a direct needs assessment survey; to describe POC test menus useful in the small-world network; and to assess strategies for preparedness following the 2004 Tsunami. METHODS: We surveyed medical professionals in community hospitals, a regional hospital, and the Naval Base Hospital; and officials at the offices of Provincial Public Health and Disaster Prevention and Mitigation. Questions covered: a) demographics and test requirements, b) POC needs, c) device design specifications, and d) pathogen detection options. Respondents scored choices. Scores determined priorities. RESULTS: Respondents selected complete blood count, electrolytes/chemistry, blood type, oxygen saturation (by pulse oximeter), hematocrit, and microbiology as top priorities, and preferred direct blood sampling with cassettes. Cardiac biomarkers were important in alternate care facilities. Staphylococcus aureus, SARS, Streptococcus pneumoniae, and hepatitis B were top infectious disease problems. Temperature, vibration, humidity, and impact shock were four important environmental conditions during extreme conditions. CONCLUSIONS: Point-of-care testing can be used on a daily basis for competency and efficiency. Familiarity improves preparedness. Instrument designs must anticipate user preferences and environment stresses. The results show how a region at risk can adapt its small-world network. Point-of-care testing has become an important risk-reducing modality for crises and works equally well in low-resource settings to speed the delivery of routine and urgent care.